Direct observation of recrystallization mechanisms during annealing of Cu in low and high strain conditions. (15th March 2018) - Nye, A.; Leff, A.C.; Barr, Christopher M.; Taheri, M.L.
Abstract: Recrystallization and subsequent twin formation in > 99.99% pure copper is investigated by in situ annealing in a scanning electron microscope. Distinct microstructural evolution mechanisms are observed for specimens deformed using 5% and 25% cold-rolled reductions. Upon annealing the former, growth and twinning of existing grains via strain-induced boundary migration is observed while the latter exhibits nucleation and growth. Serial sectioning indicates that recrystallization in the low strain condition is surface dominant while nucleation occurs through thickness in the high strain condition. Geometrically necessary dislocation densities are calculated and mapped to identify the localized driving pressures for each recrystallization mechanism. Graphical abstract: Image 2